First record of the myrmicine ant genus Syllophopsis Santschi, 1915 (Hymenoptera: Formicidae) from India with description of a new species - Akbar, Shahid Ali; Bharti, Himender; Kanturski, Mariusz; Wachkoo, Aijaz Ahmad (Zootaxa, 2021)
Here we describe and illustrate Syllophopsis peetersi sp. nov. from Silent Valley National Park, a biodiversity hotspot region of the Western Ghats of India. The discovery also marks a first native report of the genus from the Indian subcontinent. Scanning Electron Microscopy (SEM) analysis was carried out to elucidate the general morphology and sensilla of the new species. The new species is similar to congeners from Madagascar, but with larger differences from species that occur elsewhere.